Domestikasi Ikan Seluang Bebidis (Brevibora Cheeya) Dari Alam Liar Untuk Pengembangan Budidaya Ikan Hias Lokal - Aditiya, Aditiya; Natalia, Santy; Ihsan, Akmal; Saputri, Ria; Kurniawan, Ardiansyah (Jurnal Perikanan dan Kelautan, 2025)
The genus Brevibora exhibits remarkable morphological diversity, making it an interesting subject for studies in both taxonomy and its potential development as a freshwater ornamental fish. This study aimed to assess the adaptation process of the wild-caught bebidis rasbora (Brevibora cheeya) under controlled rearing conditions and to evaluate its growth performance, feed efficiency, survival rate, and water quality during the rearing period. The research was conducted from November to December 2025 using 28 individuals measuring 2–4 cm in length, reared in plastic tanks and fed commercial feed twice daily, in the morning and evening. Observed parameters included Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), Survival Rate (SR), as well as temperature, pH, and Dissolved Oxygen (DO). The results showed that B. cheeya adapted well to the artificial environment and began to accept commercial feed by the fourth day of rearing. During the 26-day rearing period, the average body weight increased from 0.70 g to 0.9 g, with an SGR of 0.96% per day, an FCR of 130, and a survival rate of 71%. Water quality parameters remained within optimal ranges, with a temperature of 26°C, pH of 6.82, and DO of 8.7 mg/L. These findings indicate that Brevibora cheeya has strong potential for development as a native ornamental fish through improved feeding strategies and refined rearing management in subsequent adaptation stages.